2012
DOI: 10.1111/j.1742-1241.2012.02939.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of sepsis management guideline in a community-based teaching hospital - can education be potentially beneficial for septic patients?

Abstract: In a community based teaching hospital, implementing the surviving sepsis campaign guideline through an education programme was feasible and resulted in early therapy with aggressive fluid administration and appropriate antibiotics. The Sepsis Education Program resulted in early therapeutic interventions and contributed to the survival benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that the implementation of the EGDT protocol and SSC education program in developed countries is associated with improved outcomes, including shorter length of stay in the ICU and hospital, and even decreased mortality [10,[17][18][19] . However, the impact of these interventions on ED visits for septicemia was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that the implementation of the EGDT protocol and SSC education program in developed countries is associated with improved outcomes, including shorter length of stay in the ICU and hospital, and even decreased mortality [10,[17][18][19] . However, the impact of these interventions on ED visits for septicemia was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous clinical trials have been conducted to provide other evidence-based clinical practice protocols, such as the Surviving Sepsis Campaign (SSC) guidelines, to be delivered in education programs or different protocols control to improve patient outcomes [12][13][14][15][16] . These protocols or education programs aim to change physician behavior and guarantee that critically ill patients receive effective treatment [17][18][19][20] . The Joint Taiwan Critical Care Medicine Committee has in fact launched a nationwide education program after the publication of the SSC [21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were various reasons as to why a misdiagnosis could occur including errors by physicians. For example, physicians in non-endemic areas were usually unfamiliar with schistosomiasis (Nguyen et al 2012), and hence, misdiagnosis might occur (Huang and Manderson 2005). Therefore, it was very necessary for physicians to conform to guidelines to diagnose patients with advanced schistosomiasis japonica.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies show a decreased mortality with correct implementation goal-directed therapy for severe sepsis(Puskarich et al, 2009;Levy et al, 2010;Patel et al, 2010;Westpahl et al, 2011;Nguyen et al, 2012; …”
mentioning
confidence: 99%